Do Assessments of HIV Risk Behaviors Change Behaviors and Prevention Intervention Efficacy? An Experimental Examination of the Influence of Type of Assessment and Risk Perceptions. Issue 3 (11th November 2014) - Glasman, Laura R.; Skinner, Donald; Bogart, Laura M.; Kalichman, Seth C.; McAuliffe, Timothy; Sitzler, Cheryl A.; Toefy, Yoesrie; Weinhardt, Lance S.
Abstract: Background: Behavioral assessments may change behaviors and responses to behavioral interventions, depending on assessment type and respondents' motivations. Purpose: We observed effects on sexual behavior and human immunodeficiency virus (HIV) prevention intervention efficacy of interviews assessing recent HIV risk behavior frequency or HIV risk behavior events among respondents with different perceptions of their risk for HIV. Methods: Young South African sexually transmitted infection (STI) clinic clients ( N  = 1, 728) participated in a 3 (event-based vs. frequency-based vs. no interview) by 2 (evidence-based vs. standard of care risk-reduction session) RCT. Results: The interviews increased reported safer sexual behavior among youth with higher but not lower risk perceptions. The intervention session was less effective when combined with interviews, particularly among lower risk perception youth. Patterns replicated for both interviews. Conclusions: HIV risk behavior assessments may increase resistance to interventions among unmotivated youth and enhance safer sexual behavior among motivated youth. Behavioral assessments may reduce HIV risk among motivated individuals.